1999
DOI: 10.1038/17833
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a DNA-bound Ultrabithorax–Extradenticle homeodomain complex

Abstract: During the development of multicellular organisms, gene expression must be tightly regulated, both spatially and temporally. One set of transcription factors that are important in animal development is encoded by the homeotic (Hox) genes, which govern the choice between alternative developmental pathways along the anterior-posterior axis. Hox proteins, such as Drosophila Ultrabithorax, have low DNA-binding specificity by themselves but gain affinity and specificity when they bind together with the homeoprotein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
312
2
5

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(345 citation statements)
references
References 29 publications
26
312
2
5
Order By: Relevance
“…In all four structures the trajectory of the DNA backbone deviates from B-form DNA at the core GA base step within the Exd/Pbx1 binding site. This base step is critical for Exd/Pbx1 binding as observed in the crystal structure (32)(33)(34)(35) as well as our own comprehensive CSI microarray studies (46).…”
Section: Dna Groove Dimensions In Hox-exd/pbx1 Structuresmentioning
confidence: 67%
See 1 more Smart Citation
“…In all four structures the trajectory of the DNA backbone deviates from B-form DNA at the core GA base step within the Exd/Pbx1 binding site. This base step is critical for Exd/Pbx1 binding as observed in the crystal structure (32)(33)(34)(35) as well as our own comprehensive CSI microarray studies (46).…”
Section: Dna Groove Dimensions In Hox-exd/pbx1 Structuresmentioning
confidence: 67%
“…Most of this cooperative interaction is the result of a conserved N-terminal YPWM tetrapeptide on the Hox protein binding into a pocket on the Exd/Pbx1 homeodomain ( Figure 1, panel a). In addition to this direct interface between Hox and Exd/Pbx1, crystal structures of four Hox-Exd/Pbx1-DNA complexes reveal a discernible perturbation of DNA geometry in the ternary complex (32)(33)(34)(35). Importantly, there is compelling evidence that Hox-Exd-DNA complex may not require interaction between the Hox N-terminal docking peptide and Exd (28,36).…”
mentioning
confidence: 99%
“…Structural analyses have shown that the HD can self-fold, and form a structural motif called a "helix-turn-helix motif." Through this motif, the HD, a DNA binding domain, recognizes a typical core DNA sequence, typically TAATor TTAT, and regulates the expression of target genes, many of which play a role in axial development (Gehring et al 1994;Krumlauf 1994;Gruschus et al 1999;Passner et al 1999).…”
Section: Hox Genesmentioning
confidence: 99%
“…Significantly, it has been possible to uncouple the two processes by using an AbdA variant mutated in the hexapeptide (Monier B, Merabet S, Perrin L, Sémériva M, unpublished data), a peptide motif required for Hox binding to their cofactor Exd. 72,73 Mutation of this domain does not affect cell lineage choice at stages 8-10, or activation of wg expression in Svp-cells at stage 16. However, the integrity of the motif is required for activation of Ih in Tin-cells at stage 16.…”
Section: A Steroid-dependent Modification Of Hox Activities Drives Thmentioning
confidence: 99%